Effect Of The Application Of Dried Slurry On Yield And Chemical Composition Of Maize Fodder (Zea Mays) (Bangladesh Journal of Animal Science, 2012)
The experiment was carried out to evaluate the effect of different levels of dried slurry (DS) as source of nitrogen fertilizer on yield and chemical composition of maize fodder (Zea mays). Four levels of DS (0, 10, 12 and 14 ton/ha) were applied in a Randomized Block Design (RBD). Green biomass yields was significantly higher in DS incorporated groups compared to control. The highest (P